(untitled) (Journal of Hama University, 2022)
The withdrawal of bronchial secretions from the trachea is one of the most important critical nursing interventions to maintain the openness of the airway of the patient placed on mechanical ventilation, a skill that requires the nursing staff in the intensive care unit have good knowledge to manage and improve the respiratory function of the patient in an effective and safe manner. Therefore, the current descriptive study aimed to Assess the nursing staff’s knowledge about the technique of bronchial secretions withdrawal from the trachea in critical care patients. This study was conducted on a sample of 45 nurses in the general critical care, chest and cardiac departments in both the National Hospital and Tishreen University Hospital in Lattakia, and they were selected using a non-randomly convenient sampling method using a questionnaire developed by the researcher. This study found that all the nursing staff in the study had a poor level of knowledge about the technique of withdrawing bronchial secretions from the trachea, as a small percentage of them knew that the withdrawal of secretions from the trachea should be repeated when needed and the catheter should be changed after each withdrawal. And that the nerve that is stimulated during the process of withdrawing secretions from the trachea is the vagus nerve. It recommended conducting periodic training and educational courses for nurses on bronchial secretions withdrawal, conducting similar studies on a larger sample in several governorates, and studying the factors affecting the nurses’ level of knowledge.